2021
DOI: 10.1007/s00586-021-06920-2
|View full text |Cite
|
Sign up to set email alerts
|

Cervical endplate bone density distribution measured by CT osteoabsorptiometry and direct comparison with mechanical properties of the endplate

Abstract: Purpose Intervertebral device subsidence is one of the complications of anterior cervical discectomy and fusion. The biomechanical properties of vertebral bony endplate may be related to device subsidence. The aim of this study is to measure the cervical endplate bone density distribution using a novel 3D measurement method. Methods Eight human cadaver cervical spines were obtained and levels C3-C7 were dissected and CT scanned. Threedimensional (3D) CT model was created with the same 3D coordinates of the ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…During full-text review, study citations were examined, and 20 articles were identified and included. A total of 186 papers 29–31,33–215 were included for data extraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During full-text review, study citations were examined, and 20 articles were identified and included. A total of 186 papers 29–31,33–215 were included for data extraction.…”
Section: Resultsmentioning
confidence: 99%
“…We did not identify any studies that compared in vivo and ex vivo biomechanical studies. At least 5 studies recommended that validation research comparing in vivo and ex vivo biomechanical properties was needed 43,97,118,162,204 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a biomechanical study showed that overall mechanical strength and stiffness and HU in the superior endplate of the caudal vertebra were lower than those in the inferior endplate of the cranial in the same intervertebral disc. Because of the significant correlation between the cervical endplate HU and the mechanical properties of the endplate, a higher incidence of subsidence in the lower endplate was observed clinically [ 35 ]. We measured the HU value of the upper and lower vertebral body and endplate, included more BMD related factors, and concluded that the HU value of the lower vertebral body was an independent risk factor for TMC subsidence.…”
Section: Discussionmentioning
confidence: 99%
“…High mechanical strength was substantially linked with high density regions of the acetabulum and femoral head (SBP correlation coefficients ranged from 0.77 to 0.97 for FL and 0.97 to 0.96 for CF) ( Hoechel et al, 2013 ). Several researchers have discovered a link between the density distribution and mechanical strength of the talar dome ( Leumann et al, 2015 ), cervical vertebral body ( Hara et al, 2021 ), and upper and lower cervical endplate ( Orías et al, 2021 ). Yet, we are aware that, while there is a strong association between the two in this sort of research, a quantitative comparison of bone density and mechanical strength is unachievable.…”
Section: Correlation Between Bone Density and Mechanical Strengthmentioning
confidence: 99%